The Effect Of Jumble Computer Software On Students’ Mastery Of English Expressions, Learning Motivational Intensity And Perceived Learning At SMPN 23 Poleang Utara - Asruni, Asruni; Hanafi, Hilaluddin; Alberth, Alberth (Halu Oleo University, 2018)
The research is aimed to: 1) find out whether there is significant effect of Jumble computer software on students’ mastery of English expression; 2) find out whether there is significant effect of Jumble computer software on students’ learning motivational intensity; 3) find out whether there is significant effect of jumble computer software on students’ perceived learning. The study employed quantitative approach through quasi experimental design. Total of sample in this study were 60 students consisted of two classes and which is selected through total sampling. The instruments used in this study were test and questionnaire. The result of data analysis revealed several conclusions. First, there is significant gain scores different between students taught using Jumble computer software and those who do not (p-value = 0.000 ≤ 0.05). Second, students’ learning motivation after taught using Jumble Computer Software is placed in high category. It is maintained by the result of one sample t-test that students ‘learning motivation is placed in high category (p-value = 0.002 ≤ 0.05). Last, students ‘perceived learning after taught using Jumble Computer Software is placed in high category. It is maintained by the result of one sample t-test that students ‘learning motivation is placed in high category (p-value = 0.001 ≤ 0.05). The pedagogical implications are that this software can be used as a competitive game in the context of teaching English expressions as well as being able to find out students' ability in mastering English expressions using this software.